2010
DOI: 10.2215/cjn.08561109
|View full text |Cite
|
Sign up to set email alerts
|

Thigh Grafts Contribute Significantly to Patients' Time on Dialysis

Abstract: Background and objectives: Thigh grafts are placed in hemodialysis patients who have exhausted all arm access sites. The goal of this study was to compare the survival, complication rates, and overall contribution of thigh grafts with arm grafts and fistulas in patients with at least one functional thigh graft during their dialysis history.Design, setting, participants, & measurements: This longitudinal review of a prospectively acquired clinical database included 85 thigh graft recipients. The rates of surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
6
36
1
Order By: Relevance
“…This rate is similar to the 3%-8.1% rates reported by two other studies (11,13). We have previously noted a higher technical failure rate in thigh grafts than in upper-extremity grafts (5), whereas another group reported a lower rate in thigh grafts (13).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This rate is similar to the 3%-8.1% rates reported by two other studies (11,13). We have previously noted a higher technical failure rate in thigh grafts than in upper-extremity grafts (5), whereas another group reported a lower rate in thigh grafts (13).…”
Section: Discussionsupporting
confidence: 90%
“…These findings closely agree with those of three large series (.100 thigh grafts) that reported secondary graft survival rates of 68%-78% at 1 year, 54%-64% at 2 years, and 46%-51% at 5 years (Table 5). In fact, two prior observational studies observed secondary survival of thigh grafts to be similar or superior to that obtained with upper-extremity grafts (5,13). Moreover, as our study demonstrated, thigh graft survival is far superior to that obtained with tunneled dialysis catheters.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Geenen et al (28) reported a 27% infection rate in the largest reported series of 153 LE-AVGs. In a longitudinal follow-up of 268 accesses over 8 years, Ram et al (21) reported that thigh AVGs survived longer than upper arm AVGs and upper arm AVFs (47% versus 11% and 3% at 5 years, respectively; P,0.01), adding significant survival time on dialysis and longevity for these patients.…”
Section: Long-term Benefits Of Le-avgmentioning
confidence: 99%